Mejorar el pensamiento reflexivo de los estudiantes a través del juego al aire libre y el aprendizaje contextual basado en juegos - Nur Riski Hasanah; Turmudi, Turmudi; Juandi, Dadang; Lessa Roesdiana (Retos (Madrid), 2025)
Integrating cognitive, affective, physical, and social aspects of learning helps introduce new ideas and consolidate existing thinking. Games and play can enhance reflective thinking skills in mathematics education. Games in mathematics teaching contribute to cognitive development and provide dynamic strategies for learning. Reflective thinking is one of the essential skills that mathematics students must possess. One method to foster reflective thinking is by applying outdoor contextual learning activities. This study aims to determine reflective thinking and the factors influencing through play and games-based contextual learning. This research method is descriptive and quantitative, with subjects of as many as 231 mathematics students determined based on a purposive sampling technique. The instrument used to collect data was the reflective thinking instrument developed by Kember. Data analysis was carried out using SEM modeling assisted by SmartPLS. Based on the data analysis results, it is known that understanding is the most influential indicator of reflective thinking, with a path coefficient value of 0.404 and a t-statistic > t-table of 19.430 > 1.653. Meanwhile, habitual action is the indicator with the lowest influence, with a path coefficient value of 0.129 and t-statistic > t-table of 3.818 > 1.653. In addition, critical reflection and reflection have a significant effect based on the path coefficient values of 0.330 and 0.381, respectively. This shows that the four indicators significantly influence the reflective thinking of mathematics teacher students.